Development of (quinolinyl)amido-based pincer palladium complexes: a robust and phosphine-free catalyst system for C–H arylation of benzothiazoles - Pandiri, Hanumanprasad; Soni, Vineeta; Gonnade, Rajesh G.; Punji, Benudhar (New Journal of Chemistry, 2017)
(Quinolinyl)amido-ligated palladium(II) complexes have been synthesized and applied in the catalytic C–H bond arylation of benzothiazoles. The tridentate ligand precursors R2N-C(O)CH2-(NH)-C9H6N [(R2NNN8-Q)–H; R2N = morpholinyl, Me-N-piperazinyl] and the pincer palladium complexes [κN,κN,κN-{R2N-C(O)CH2-(μ-N)-C9H6N}]PdX [(R2NNN8-Q)PdX {R2N = Et2N, morpholinyl, Me-N-piperazinyl; X = OAc or Cl}] were efficiently synthesized, and characterized by various analytical techniques. The iodo derivative (Et2NNN8-Q)PdI was obtained in excellent yield by the treatment of the complex (Et2NNN8-Q)PdCl with KI. The molecular structures of complexes (Et2NNN8-Q)Pd(OAc) (2a), (Et2NNN8-Q)PdCl (3a) and (Et2NNN8-Q)PdI (4a) were elucidated by X-ray crystallography. Complex 3a was found to be the most efficient catalyst for direct C–H bond arylation of substituted benzothiazoles with diverse aryl iodides using a mild base, K2CO3. The working catalyst system 3a is highly robust and can be recycled and reused several times for the arylation of benzothiazole without loss of catalytic activity. Preliminary mechanistic investigations using controlled studies and kinetic analysis have been performed, which greatly support a molecular mechanism for the arylation.

Synthesis of quinolinyl based pincer copper (II) complexes: an efficient catalyst system for Kumada coupling of alkyl chlorides and bromides with alkyl Grignard reagents - Pandiri, Hanumanprasad; Gonnade, Rajesh G.; Punji, Benudhar (Dalton Transactions, 2018)
Quinolinamide-based pincer copper(ii) complexes, (N),(N),(N)-{C9H6N-(-N)-C(O)CH2NEt2}CuX [((NNN2Et)-N-Q)CuX (X = Cl, 2; X = Br, 3; X = OAc, 4)], were synthesized by the reaction of ligand ((NNN2Et)-N-Q)-H (1) with CuX2 (X = Cl, Br or OAc) in the presence of Et3N. The reaction of ((NNN2Et)-N-Q)-H with CuX (X = Cl, Br or OAc) also afforded the Cu(ii) complexes 2, 3 and 4, respectively, instead of the expected Cu(i) pincer complexes. The formation of Cu(ii) complexes from Cu(i) precursors most likely occurred via the disproportionation reaction of Cu(i) into Cu(0) and Cu(ii). A cationic complex [((NNN2Et)-N-Q)Cu(CH3CN)]OTf (5) was synthesized by the treatment of neutral complex 2 with AgOTf. On the other hand, the reaction of ((NNN2Et)-N-Q)-H (1) with [Cu(MeCN)(4)]ClO4 produced cationic Cu(i) complex, [((NN)-N-Q(H)N-2(Et))Cu(CH3CN)]ClO4 (6), in good yield. All complexes 2-5 were characterized by elemental analysis and HRMS measurements. Furthermore, the molecular structures of 2, 3 and 4 were elucidated by X-ray crystallography. Complex 4 crystallizes in a dimeric and catemeric pattern. The cationic complex 5 was found to be an efficient catalyst for the Kumada coupling reaction of diverse nonactivated alkyl chlorides and bromides with alkyl magnesium chloride under mild reaction conditions.